2021
DOI: 10.1371/journal.pone.0248784
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of health insurance policy and behavior in a virtual environment

Abstract: We introduce a new experimental approach to measuring the effects of health insurance policy alternatives on behavior and health outcomes over the life course. In a virtual environment with multi-period lives, subjects earn virtual income and allocate spending, to maximize utility, which is converted into cash payment. We compare behavior across age, income and insurance plans—one priced according to an individual’s expected cost and the other uniformly priced through employer-implemented cost sharing. We find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Adoption is further hindered by the lack of alignment between other organizational actors in the network, such as insurance payers and hospitals. Even though models have shown that preventative programs can improve outcomes, reliance on actuarial models, misaligned incentives between the insurance industry and providers, and short-term views all contribute to reluctance on the part of insurance companies to support new protocols and preventative methods (Tracy et al, 2021;Goldman et al, 2004;Cichon et al, 1999;Herzlinger, 2006;Horne & Savage, 2020). The voters and the patient population are also not informed enough to be active advocates of its evolution (Hermes et al, 2020).…”
Section: Figure 33 Dhi Policy Mapmentioning
confidence: 99%
“…Adoption is further hindered by the lack of alignment between other organizational actors in the network, such as insurance payers and hospitals. Even though models have shown that preventative programs can improve outcomes, reliance on actuarial models, misaligned incentives between the insurance industry and providers, and short-term views all contribute to reluctance on the part of insurance companies to support new protocols and preventative methods (Tracy et al, 2021;Goldman et al, 2004;Cichon et al, 1999;Herzlinger, 2006;Horne & Savage, 2020). The voters and the patient population are also not informed enough to be active advocates of its evolution (Hermes et al, 2020).…”
Section: Figure 33 Dhi Policy Mapmentioning
confidence: 99%